Recurrent Hypocalcemic Tetany as the Initial Presentation in Some Persons with Hyperthyroidism: A Case Series - Yakubu Lawal; Umar Faruk Dahuwa; Ibrahim Abdullahi; Felicia Ehusani Anumah (Dubai Diabetes and Endocrinology Journal)
This is a case series of recurrent hypocalcemic tetany as the initial presentation in some cases of hyperthyroidism. Literature review has revealed more reports of hypercalcemia than hypocalcemia as a feature of hyperthyroidism. The recurrence of hypocalcemic tetany in the 3 cases reported ceased following the treatment of hyperthyroidism. The aim of this case series is to alert clinicians to the fact that hypocalcemic tetany can be the initial clinical presentation of hyperthyroidism. It also highlights the resilience of managing endocrine patients in resource-poor settings with the aid of high clinical acumen and fewer-than-expected laboratory investigations. Further research is needed to investigate our hypothesis that disordered calcium metabolism in thyrotoxicosis may manifest in successive phases of hypercalcemia-normocalcemia-hypocalcemia. The rate at which individual thyrotoxic patient traverses these phases may be directly proportional to the background vitamin D deficiency, negative calcium balance, and bone mineral density.